BEYOND PROMOTIONS AND STORE ATMOSPHERE: BRAND IMAGE DRIVES PURCHASES AT WARUNG MADURA - Davina Shafa Felisa; K. Emi Trimiati (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
Introduction: Warung Madura is a community-based convenience retail format operated predominantly by Madurese entrepreneurs and characterized by extended operating hours, accessible neighborhood locations, fast service, and the availability of daily necessities. Despite its rapid growth in urban retail markets, limited empirical evidence explains which marketing factors shape consumers’ purchase decisions in this informal retail format. This study examines the effects of promotion, store atmosphere, and brand image on purchase decisions at Warung Madura in East Semarang. Methods: A quantitative explanatory design was employed using a structured questionnaire distributed to 100 consumers who had purchased products from Warung Madura within the previous week. Data were analyzed using IBM SPSS Statistics 27 through validity and reliability testing, classical assumption tests, and multiple linear regression. Results: Promotion and store atmosphere show positive but insignificant effects on purchase decisions, whereas brand image has a positive and significant effect and emerges as the dominant predictor. The model explains 55.9% of the variance in purchase decisions. Discussion: The findings indicate that purchase decisions in Warung Madura are driven more by trust, familiarity, reliability, and collective brand perception than by formal promotion or physical store ambience. This study extends retail marketing literature by highlighting brand image as a key strategic asset in community-based convenience retail